Les silences du dialogue romanesque dans Moderato Cantabile de Marguerite Duras - Timenova-Valtcheva, Zlatka (Verbum – Analecta Neolatina, 2009)
This paper deals with the silences of dialogue in Moderato Cantabile by Marguerite Duras. The starting hypothesis is that silence is a phenomenon of constructive and significant absence which could justify a choice of writing. The concrete question which we would like to analyze is how fictional dialogue creates meaningful silences.